Study of association between body composition and anthropometric dimensions in a population of Indian Army - Inderjeet Singh; L Robert Varte; Shweta Rawat (Al Ameen Medical College, 2014)
Objectives: To investigate the association of various anthropometric measures with body composition parameters such as percentage of body fat (PBF), fat mass (FM) and fat free mass (FFM). Material and method: This study was carried out on randomly selected 373 Gorkha soldiers (age range was 20-48 years) of Indian army. All anthropometric parameters were measured using calibrated anthropometer, sliding caliper, skin fold calipers and inelastic steel measuring tape. Body composition variables were recorded using BIA model TANITA, TBF-310. Result: Result indicate that waist circumference (WC) showed the strongest correlations (p=0.000) with FM (r=0.802) and PBF(r=0.758). The highest amount of variation of PBF (57.4%) and FM (64.3%) was explained by WC while hip circumference (HC) explained 37.6% and 52.6% variation of PBF and FM respectively and HC also explained 52.6% variation of FFM. Conicity index (CI) explained low variation of PBF and FM compared to WC and WHR. Conclusion: Present study showed that WC has a better association with body fat than rest anthropometric parameters including WHR and CI. Hence the use of WC instead of WHR and CI could be advantageous in study of central adiposity with PBF and FM.